Understanding The Link Between Nutritional Status and Physical Fitnes Level Among Students: Building Foundation for Health - Mardepi Saputra; Riand Resmana; Mario Febrian; Yogi Arnaldo Putra; Muhammad Fakhrur Rozi (Universitas PGRI Palembang, 2023)
This research is based on the field reality, particularly in Elementary School 04 Kajai, Pariaman City, where the level of student's physical fitness is still low. There are many factors that contribute to this, and one of the suspected factors is the student's nutritional status. The purpose of this study is to investigate the relationship between student's nutritional status and physical fitness, specifically in Elementary School 04 Kajai, Pariaman City. The research design used in this study is correlational. The population of this research consists of 72 students from Elementary School 04 Kajai, Pariaman City. The sampling technique employed was purposive sampling, resulting in a sample size of 39 students, consisting of 24 male students and 15 female students. This study utilizes primary data obtained from measurements of nutritional status and physical fitness tests, as well as secondary data from school archives. The data collection instruments include measurements of nutritional status based on Body Mass Index (BMI) and physical fitness tests such as a 40-meter run, bent-arm hang, sit and reach, standing long jump, and a 600-meter run. The data was analyzed using correlational statistics through SPSS version 10.0. The research findings indicate that (1) the correlation between nutritional status and physical fitness of male students is (rxy) 0.219 < rtab (0.404), (2) the correlation between nutritional status and physical fitness of female students is (rxy) 0.220 < rtab(0.514). Based on the research findings, it can be concluded that there is no significant relationship between nutritional status and physical fitness level among both male and female students at Elementary School 04 Kajai, Pariaman City.